Correspondence: Comments on "a first list of vespid wasps from Vietnam (Hymenoptera: Vespidae)" by Pham and Li (2015) - Phuong Lien, Nguyen Thi (Academia Journal of Biology, 2016)
Pham and Li (2015) published a list of vespid wasps from Vietnamon 26 August 2015, which included 109 species in 32 genera of four subfamilies, namely Eumeninae (33 species), Stenogastrinae (10 species), Polistinae (50 species), and Vespinae (16 species) [17]. Presently, based on the data gathered from all references published before Pham and Li (2015), a total of 131 species of vespid wasp in 39 genera has been recorded from Vietnam, including Eumeninae (56 species), Stenogastrinae (10 species), Polistinae (51 species) and Vespinae (14 species). Nguyen et al. (2014) [10] was published more than a year before Pham and Li, and provided an annotated distributional checklist of solitary wasps of the subfamily Eumeninae of Vietnam, which listed 45 species in 26 genera, including 13 species and six genera that were newly recorded for Vietnam. In the same year, one more species in the group was described as new in Nguyen & Xu (2014) [16] [Okinawepipona nigra Nguyen & Xu, 2014]. So by the end of 2014, 46 species of Eumeninae were recorded from Vietnam. By the end of 2014, a total of 74 identified species in 11 genera of social wasps in the three subfamilies Stenogastrinae, Polistinae and Vespinae was recorded from Vietnam, including 10 species in Stenogastrinae, 50 species in Polistinae and 14 species in Vespinae (Nguyen et al., 2006a,b; Nguyen, 2007; Nguyen & Kojima, 2013; Nguyen, 2014) [14, 15, 12, 4, 2]. Of the 76 species of social wasps listed in Pham and Li (2015) [17], Vespa auraria Smith, 1852 was synonymized under Vespa velutina Lepeletier, 1836, by Nguyen et al. (2006) [14]. The status of Vespa binghami du Buyson, 1905 was mentioned in Nguyen & Carpenter (2002) [9] as “the presence of this species in Vietnam, while possible, is not documented”, but this species was still listed in Pham & Li (2015) [17] without any additional information. Thus, only 74 presently recognized species of social wasps were listed in Pham & Li (2015) [17]. Furthermore, Polistes meadeanus (von Schulthess, 1913) was recorded in Vietnam by Nguyen (2014) [4] but was not listed in Pham & Li (2015) [17]. Moreover, Polybioides gracilis van der Vecht, 1966, was confirmed to occur in Vietnam (Gia Lai province) according to Nguyen (2013) [3] and Nguyen et al. (2014b) [11], but was also not mentioned in Pham & Li (2015) [17]. So if all published literature to end of 2014 is considered, the numbers of all vespid wasps in all four subfamilies given in Pham and Li (2015) were known to be wrong. After Nguyen et al. (2014) [10], and by the end of June 2015, several publications on solitary wasps were published, including Nguyen & Xu (2014) [16], Nguyen (2015a, b, c, d) [5, 6, 7, 8] (all mentioned publications were published by the end of June 2015). Based on those references, a total of 56 solitary wasp species in 28 genera of the subfamily Eumeninae has been recorded from Vietnam, including 44 species listed in Nguyen et al. (2014a) [10] [one taxon, Anterhynchium abdominale abdominale (Illiger) was described as new to science in Nguyen (2015c) [7], the species listed in Nguyen & Xu (2014) [16] [Okinawepipona nigra Nguyen &Xu, 2014], one species listed in Nguyen (2015a) [5] [Delta conoideum (Gmelin, 1790)], 2 species listed in Nguyen (2015b) [6] [Pararrhynchium striatum Nguyen, 2015 and P. concavum Nguyen, 2015], 3 species listed in Nguyen (2015c) [7] [Anterhynchium punctatum Nguyen, 2015, A. (Dirhynchium) flavolineatum flavolineatum (Smith, 1857) and A. (Dirhynchium) flavomarginatum flavomarginatum (Smith, 1852)], and 5 species listed in Nguyen (2015d) [8] [Eumenes atrophicus (Fabricius, 1798), E. gibbosus Nguyen, 2015, E. inconspicuus Smith, 1858, E. labiatussinicus Giordani Soika, 1941, and E. rubronotatus Pérez, 1905], compared to 32 species of the subfamily listed in Pham & Li (2015) [17] [of the 33 species of solitary wasps listed in Pham & Li (2015), Eumenes flavopictus continentalis (Zimmermann, 1931) was synonymized under Phimenes flavopictum flavopictum by Kumar (2013) [1]. By the end of June 2015, a total of 79 identified species in 11 genera of the three social wasp subfamilies Stenogastrinae, Polistinae and Vespinae was recorded from Vietnam, compared to 74 species listed in Pham & Li (2015) [17]. Of the 79 species, 74 species were recorded from the past upto end of 2014. In addition, 5 species of the genus Parapolybia were listed in Saito-Morooka et al. (2015) [18] [Parapolybia albida Saito-Morooka, Nguyen & Kojima, P. bioculata van der Vecht, 1966, P. flava Saito-Morooka, Nguyen & Kojima, 2015, P. nana Saito-Morooka, Nguyen & Kojima, 2015, and P. tinctipennis (Cameron, 1900)], but not listed in Pham & Li (2015) [17]. So if all pertinent literature before Pham and Li (2015) was even published was cited, the numbers of all vespid wasps in four subgenera given in Pham and Li (2015) were known to be wrong and out of date. The distribution records of all species listed in Pham & Li (2015) were presented in previous publications excludingsome additional records of some widelydistributed species. For all of the above reasons, the list given in Pham & Li (2015) was an incomplete checklist of vespid wasps from Vietnam and contributed little to the knowledge of vespid wasps in Vietnam.